2019
DOI: 10.1002/stem.2978
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of von Willebrand Factor Gene in Endothelial Cells That Are Programmed to Pluripotency and Differentiated Back to Endothelial Cells

Abstract: Endothelial cells play a central role in physiological function and pathophysiology of blood vessels in health and disease. However, the molecular mechanism that establishes the endothelial phenotype, and contributes to its signature cell type-specific gene expression, is not yet understood. We studied the regulation of a highly endothelial-specific gene, von Willebrand factor (VWF), in induced pluripotent stem cells generated from primary endothelial cells (human umbilical vein endothelial cells [HUVEC] into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…It is reported that 3D scaffolds hold the potential to promote blood vessel formation and bone formation [60][61][62], although BMP9-mediated blood vessel formation was identified by both in vitro and in vivo tests, it is still necessary to investigate BMP9-mediated bone formation with the use of 3D scaffolds to further construct BMP9-mediated bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 3D scaffolds hold the potential to promote blood vessel formation and bone formation [60][61][62], although BMP9-mediated blood vessel formation was identified by both in vitro and in vivo tests, it is still necessary to investigate BMP9-mediated bone formation with the use of 3D scaffolds to further construct BMP9-mediated bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…The initial dataset contained 49,400 observations for 19,929 unique genes [ 17 , 18 ]. Each observation had multiple gene expression values corresponding to induced pluripotent cells, differentiated endothelial cells and differentiated neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
“…A potential approach towards addressing this gap in knowledge is to compare the molecular signature of two distinct cell lineages that are derived from one parental stem cell, thus possessing a similar genetic background with each other as well as with the parental stem cell. We have previously reported the generation of induced pluripotent stem cells (iPS) from human umbilical vein endothelial cells (HUVEC) the and subsequent differentiation of the resulting iPS (referred to as HiPS) back into a highly pure population of endothelial cells (Ec-Diff), as well as a population of neural cells that contained both neurons and astrocytes (Nn-Diff) [ 17 , 18 ]. Although the Nn-Diff were a mix of both neurons and astrocytes, their common neural phenotype is clearly distinct from endothelial cells, and thus they provide an appropriate comparator to the highly pure endothelial population of Ec-Diff.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations